2018
DOI: 10.3390/antibiotics7030060
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Antibiotic Resistant Gonorrhoea in the United Kingdom

Abstract: Gonorrhoea is one of the most common sexually-transmitted bacterial infections, globally and in the United Kingdom. The levels of antibiotic resistance in gonorrhoea reported in recent years represent a critical public health issue. From penicillins to cefixime, the gonococcus has become resistant to all antibiotics that have been previously used against it, in each case only a matter of years after introduction as a first-line therapy. After each instance of resistance emergence, the treatment recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 77 publications
1
26
0
Order By: Relevance
“…Whole-genome sequencing (WGS) analysis confirmed the results of 23S rRNA (A2059G) mutation and a mosaic-mtr locus obtained by PCR and Sanger sequencing, and it revealed that the mosaicism seen in the mtr locus extended through a large part azithromycin as part of the current treatment regimen (3,6). In recent years, many countries have observed an increase in the prevalence of reduced susceptibility to azithromycin in N. gonorrhoeae.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Whole-genome sequencing (WGS) analysis confirmed the results of 23S rRNA (A2059G) mutation and a mosaic-mtr locus obtained by PCR and Sanger sequencing, and it revealed that the mosaicism seen in the mtr locus extended through a large part azithromycin as part of the current treatment regimen (3,6). In recent years, many countries have observed an increase in the prevalence of reduced susceptibility to azithromycin in N. gonorrhoeae.…”
Section: Resultsmentioning
confidence: 56%
“…A ntimicrobial agents play a critical role in the fight against gonorrhea, a sexually transmitted disease caused by Neisseria gonorrhoeae. The use of antibiotics for gonorrhea management began in the mid-1930s (1)(2)(3). This date also marked the dawn of a perpetual battle against antibiotic-resistant N. gonorrhoeae (AR-Ng).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, through epistatic interactions with other genetic variants) within and/or across different antibiotics when screening for a novel resistance variant. For example, as ciprofloxacin was the recommended first-line therapy for uncomplicated gonorrhea through 2005 in the United Kingdom 46 , 2007 in the United States 47 , and more recent years in other countries 4850 , we investigated whether resistance to ESCs is significantly more likely to occur in the background of genotypic ciprofloxacin resistance ( i.e. , in strains with the GyrA S91F mutation).…”
Section: Resultsmentioning
confidence: 99%
“…1 In England there is a growing epidemic of gonorrhoea, while treatment is becoming harder, particularly among men who have sex with men (MSM). 2 In 2019, rising azithromycin resistance in the UK has led to the drug's removal from the previously recommended dual therapy. 3 The remaining component, ceftriaxone, is now both the first and last line of treatment, with worrying signs that it may also fail soon.…”
Section: Introductionmentioning
confidence: 99%